Study of Secondary Spent Wash after Biogas Recovery as Biogas Effluent - Limaye, P.A.; Nimse, M.S. (Asian Journal of Chemistry, 2010)
Potash can be recovered more easily by centrifuge from secondary spent wash after concentration than the primary spent wash, secondary spent wash concentrate being less viscous and thinner. About 6 tons of potash in good form can be daily obtained against about 7 tons from primary spent wash. Carbon that can be obtained by the method already used though less than primary spent wash is sufficient to pose problems of pollution. daily about 8 to 10 tonnes of carbon will be available.